1994
DOI: 10.1002/pro.5560031225
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide crosslinks to probe the structure and flexibility of a designed four‐helix bundle protein

Abstract: The introduction of disulfide crosslinks is a generally useful method by which to identify regions of a protein that are close together in space. Here we describe the use of disulfide crosslinks to investigate the structure and flexibility of a family of designed 4-helix bundle proteins. The results of these analyses lend support to our working model of the proteins' structure and suggest that the proteins have limited main-chain flexibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…It has been suggested that because the rn value reflects the difference in the amount of denaturant bound to the denatured versus the folded protein, differences in m values within a series of mutants may reflect differences in the solvent-accessible hydrophobic surface area that is exposed upon unfolding (Schellman, 1978). This interpretation is supported by the observation that the introduction of a disulfide bridge in a protein decreases the magnitude of the protein's m value (Villafranca et al, 1987;Pace et a!., 1988;Betz & Pielak, 1992;Regan et al, 1994). Furthermore, for several proteins the magnitude of the m value correlates with the heat capacity change that is associated with protein unfolding (ACp) (Myers et al, 1995).…”
Section: Equilibrium Guhcl Denaturation: Circular Dichroismmentioning
confidence: 99%
“…It has been suggested that because the rn value reflects the difference in the amount of denaturant bound to the denatured versus the folded protein, differences in m values within a series of mutants may reflect differences in the solvent-accessible hydrophobic surface area that is exposed upon unfolding (Schellman, 1978). This interpretation is supported by the observation that the introduction of a disulfide bridge in a protein decreases the magnitude of the protein's m value (Villafranca et al, 1987;Pace et a!., 1988;Betz & Pielak, 1992;Regan et al, 1994). Furthermore, for several proteins the magnitude of the m value correlates with the heat capacity change that is associated with protein unfolding (ACp) (Myers et al, 1995).…”
Section: Equilibrium Guhcl Denaturation: Circular Dichroismmentioning
confidence: 99%
“…3 and 4). While the effect of the disulfide bridge on stability is difficult to interpret because it involves the comparison of a bimolecular concentration-dependent unfolding process for the reduced coiled-coil and a unimolecular concentration-independent unfolding process for the oxidized coiled-coil (Regan et al, 1994), we have estimated the interchain disulfide bridge to offer about 3-4 kcal/mol additional stability to the coiled-coil (Hodges et al, 1990;Kohn et al, 1995). This effect would be expected to be capable of counteracting a large number of interchain electrostatic repulsions, which as stated above have been estimated to destabilize by 0.45 kcal/mol per Glu-Glu repulsion.…”
mentioning
confidence: 99%
“…This effect was demonstrated in many studies in which disulfide formation was used as a probe for structure and flexibility of proteins (for a recent work, see Ref. 17). The precomplex only needs to be short-lived because dissociation of the final complex is rendered impossible by the disulfide bridges.…”
Section: Discussionmentioning
confidence: 99%